Insights into gut microbiota metabolism of dietary lipids: the case of linoleic acid. Issue 8 (29th March 2022) - Huyan, Zongyao; Pellegrini, Nicoletta; Steegenga, Wilma; Capuano, Edoardo
Abstract : In this study we explored the effect of chemical form and incorporation in a plant matrix on microbial metabolism of linoleic acid by monitoring the formation of potentially bioactive metabolites in an in vitro model of colonic fermentation. Abstract : It has been recognized that, next to dietary fibre and proteins, gut microbiota can metabolize lipids producing bioactive metabolites. However, the metabolism of dietary lipids by human gut microbiota has been poorly explored so far. This study aimed to examine the change in lipids, particularly linoleic acid (LA), induced by the chemical form of lipids and the presence of the plant matrix. Short-chain fatty acid (SCFA) production was monitored to get an insight into microbial activity. Free LA, glyceryl trilinoleate and soybean oil as well as digested intact (DS) and broken (BS) soybean cells were subjected to in vitro fermentation using human faecal inoculums. Confocal microscopy was used to visualize the soybean cell integrity. Three LA metabolites, including two conjugated fatty acids (CLAs, 9z, 11e and 9e, 11e) and 12hydroxy, 9z C18:1, were identified and monitored. Free LA addition improved the LA metabolite production but reduced SCFA concentrations compared to trilinoleate and soybean oil. Breaking cell integrity had impacts on CLA, hydroxy C18:1 and SCFA production and free fatty acid release within the first 24 h of fermentation, but this effect vanished with time. In contrast, soybean oil only increased free LA release and hydroxy C18:1 production. The content of several FAs decreased during fermentation suggesting a substantial conversion in microbial metabolites. Besides, LA metabolites were also identified in the fermentation pellets suggesting the incorporation of microbial FA metabolites into bacterial cells. This study expands our understanding of microbial metabolism of dietary lipids with a special emphasis on the role of food- and diet-related factors.